Caries experience among children born after a complicated pregnancy. Issue 3 (20th November 2020) - van der Tas, Justin T.; Wolvius, Eppo B.; Kragt, Lea; Rivadeneira, Fernando; Moll, Henriëtte A.; Steegers, Eric A. P.; Schalekamp‐Timmermans, Sarah
Abstract: Objectives: Behavioural and lifestyle factors, as oral hygiene and diet, are well‐established risk factors in the pathogenesis of dental caries, though displaying large differences in susceptibility across individuals. Since enamel formation already starts in utero, pregnancy course and outcome may eventually play a role in enamel strength and caries susceptibility. Therefore, we studied the association between history of pregnancy complications and the caries experience in their six‐year‐old children. The pregnancy complications included small for gestational age (SGA), spontaneous preterm birth (sPTB), gestational hypertension (GH), pre‐eclampsia (PE), individually, and a combination of those, designated as placental syndrome. Methods: This study was embedded in Generation R, a prospective longitudinal Dutch multiethnic pregnancy cohort study. Information about pregnancy complications was obtained from questionnaires completed by midwives and obstetricians with cross‐validation in medical records. These included SGA, sPTB, GH and PE. Caries experience was assessed with the decayed, missing and filled teeth (dmft) index at a mean age of six years. The association between dental caries experience and a history of pregnancy complications was studied by using hurdle negative binomial (HNB) models. Results: We were able to assess the dmft index in 5323 six‐year‐old children (mean age 6.2 years, SD 0.5). We did not find an association between the different pregnancy complications and dental caries experience in childhood, whether for SGA, sPTB, GH, PE, or for the combined outcome placental syndrome (HNB estimates: OR 1.02, 95%CI 0.87 ‐ 1.19; RR 0.90, 95%CI 0.78 ‐ 1.04). Further adjustment of the models with different confounders did not alter the outcome. Conclusions: Although it is expected that prenatal stress can be a risk factor for caries development later in life, our findings do not support this hypothesis. Therefore, we believe disparities in caries experience between children are probably not explained by early life events during a critical intrauterine period of development.